The preservation and protection of the cultural Heritage of Peru in the framework of the World Heritage Convention - Rodríguez Cuadros, Manuel (2018)
The article presents a detailed vision of the system for the protection of the cultural and natural heritage of humanity, its principles, mechanisms and courses of action. It analyzes the obligations and responsibilities assumed by Peru and the other States that are part of the 1972 Convention. It explains that the system is essentially legal, because beyond the archaeological, architectural, anthropological, geographic, historical and ethnohistorical components that entails the notion of cultural heritage, its protection is regulated and guided by legal norms of a double aspect: those that form a strictu sensu part of the national legislation and those contained in international treaties. Both required in domestic law. When evaluating the application of the system to Peruvian goods inscribed in the world heritage list, the author uses the situation of Machu Picchu as a case study and explains the strengths and vulnerabilities of its management model.